Foodscaping : practical and innovative ways to create an edible landscape - Nardozzi, Charlie (Cool Springs Press, 2015)
Keep your lawn and eat it too - Foodscaping will show you how to grow food without giving up your view. Foodscaping is what it sounds like - a combination of landscaping and food. This gardening resource is chock-full of real-world examples, photos, and advice so that even an average Joe homeowner and gardener can grow food without sacrificing either their lawn or their home's appearance to do so. While edible and ornamental aren't always synonymous, they can be combined, with the right plants, placement, and advice from author and edible gardening expert Charlie Nardozzi. Charlie's ideas allow you to add food plants wherever you like. Incorporating food-bearing plants as hedgerows and barriers or in small spaces, containers, window boxes and many more ideas allow you to expand the types of plants you can use and even extend your growing season! For example, blueberry bushes provide not just fruit, but also wonderful fall color. Arbors and pergolas are perfect supports for edible plants and even simplify harvest. Squash and cabbage have attractive, interesting leaf textures, so they can be a part of the ornamental garden. Foodscaping also goes beyond mere plant selection. The basics of gardening, planting, pruning, dealing with pests, watering, feeding, and harvesting are all covered in detail, ensuring your success in creating a beautiful, edible landscape for your home.